The Role of Social Media in Building the Image of TransJakarta: A Content Analysis of News on the Instagram Account @pt_transjakarta - Lancia, Ferrari; Puspitaningrum, Deby; Pahlevi, Muhammad Reza (Golden Ratio of Data in Summary, 2024)
Instagram is a social media platform that is highly popular among the public, and its use is not limited to individuals but also extends to organizations and companies. PT. Transportasi Jakarta (TransJakarta) uses Instagram as a tool to support its reputation and image in the eyes of the public. The purpose of this study is to understand the role of Instagram in building the image of TransJakarta and to analyze the news content on the Instagram account owned by TransJakarta. In this research, the theory and method used is media ecology theory with a qualitative research approach. The nature or type of this research is descriptive research. Data collection techniques were carried out in the form of primary and secondary data. In this study, the researcher used source triangulation as a data validation technique. From the research results, it was found that the role of public relations in enhancing the image of TransJakarta through Instagram has been effective. This is evident from the positive feedback, the growing number of followers, and the increased engagement with TransJakarta's Instagram account.